Fusion to green fluorescent protein improves expression levels of Theileria parva sporozoite surface antigen p67 in insect cells - Kaba, S.A.; Nene, Vishvanath M.; Musoke, A.J.; Vlak, J.M.; Oers, M.M. van (Cambridge University Press, 2002)
East Coast fever (ECF) is a fatal disease of cattle caused by the protozoan parasite Theileria parva. The development of a subunit vaccine, based on the sporozoite-specific surface antigen p67, has been hampered by difficulties in achieving high-level expression of recombinant p67 in a near-authentic form. Therefore two sets of recombinant baculovirus vectors were constructed. The first set, encoding various regions of p67, produced low levels of the corresponding p67 domains in High Five™ cells, despite the presence of large amounts of p67 RNA. The second, consisting of p67 domains fused to the carboxy-terminus of GFP expressed significantly higher levels of p67 protein. The GFP[ratio ]p67 fusion proteins were recognized by a sporozoite-neutralizing monoclonal antibody (TpM12) raised against native p67 whereas non-fused full length p67 expressed in insect cells was not recognized. GFP-tagging therefore, appeared to enhance the stability of p67 and to conserve its folding. The high-level expression of p67 domains in a more authentic form is an important step towards the development of an effective subunit vaccine against ECF.